PELATIHAN MEDIA PEMBELAJARAN BERBASIS ARTIFICIAL INTELEGENCE UNTUK MENINGKATKAN KREATIFITAS SISWA DI SMPN 19 MUARO JAMBI - Relawati; Amir Syarifuddin (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
The use of artificial intelligence (AI) technology in the education sector has created many opportunities for changes in learning methods that are more individual, adaptive, and effective. AI can also help teachers detect student learning difficulties early and provide appropriate intervention suggestions. such as unequal access to technology, low digital literacy among teachers and students, and ethical and data protection issues. This article aims to comprehensively analyze the potential and obstacles in the use of AI in education, while offering recommendations for sustainable and inclusive implementation strategies to enhance students' learning creativity. This article can be a reference for policy makers, teachers, and educational technology practitioners in designing AI-based learning systems to enhance student creativity.